2016
DOI: 10.1002/wsb.679
|View full text |Cite
|
Sign up to set email alerts
|

Foraging at the wildland–urban interface decouples weather as a driver of recruitment for desert bighorn sheep

Abstract: A growing number of ungulate populations are living within or near the wildland–urban interface. When resources at the interface are of greater quality than that of adjacent natural habitat, wildlife can be attracted to these developed areas. Little is known about how use of the wildland–urban interface by wildlife may affect vital rates. Under natural conditions, recruitment by desert bighorn sheep (Ovis canadensis nelsoni) correlates with variation in the timing and amount of rainfall that initiates and enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Across years, we would expect these populations to exhibit boom and bust dynamics in nest success, reflecting the erratic conditions under which they live. Similar patterns have been described for desert ungulates, in which a highly variable growing season promotes a long birthing season with only a small portion of any cohort surviving in a given year (Bunnell, 1982; Longshore, Lowery, & Cummings, 2016; Stoner et al., 2016). Low‐elevation populations are more vulnerable to poor recruitment, with future changes likely to exacerbate current trends.…”
Section: Discussionsupporting
confidence: 62%
“…Across years, we would expect these populations to exhibit boom and bust dynamics in nest success, reflecting the erratic conditions under which they live. Similar patterns have been described for desert ungulates, in which a highly variable growing season promotes a long birthing season with only a small portion of any cohort surviving in a given year (Bunnell, 1982; Longshore, Lowery, & Cummings, 2016; Stoner et al., 2016). Low‐elevation populations are more vulnerable to poor recruitment, with future changes likely to exacerbate current trends.…”
Section: Discussionsupporting
confidence: 62%
“…Deer at the wildland–urban interface were primarily active at night when nightlight exposure is most perceptible. These areas with elevated nightlight exposure also contain watered lawns, city parks and agriculture which provide elevated levels of greenness, used for forage and cover (Longshore et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Neonates that are heavier at birth typically have higher survival rates that those born lighter (Thorne et al , Fairbanks , Keech et al , Cook et al , Heffelfinger et al ). Several studies have reported a positive relationship between fall lamb:adult female ratios in desert bighorn sheep and rainfall during the previous winter period (Douglas and Leslie , Wehausen et al , Douglas , Wehausen , Longshore et al ), suggesting a link between rainfall during late gestation and early post‐parturition, and juvenile recruitment. Rainfall during the second year of our study when we observed very low lamb survival (i.e., 20%) was 68% below average compared to the first year when lamb survival was around 70% and rainfall during late gestation was almost 3 times higher than normal.…”
Section: Discussionmentioning
confidence: 98%